A Comparative Evaluation of Swedish Intensive Care Patient Rooms. (April 2014) - Apple, Michael
OBJECTIVE: This study investigates how design strategies in three recent intensive care units in Sweden impact patients, families, and staff. The area of focus is the patient room "module, " usually consisting of a pair of patient rooms and a joint location for monitoring and documentation. BACKGROUND: Many countries are expanding their number of intensive care beds and are also in the process of incorporating evidence-based design strategies such as single-bed patient rooms and access to daylight and nature. This situation provides a significant opportunity to review and learn from facilities leading the way in these areas. METHODS: Three intensive care units completed since 2010 were evaluated in relation to a combination of criteria. Methods included plan drawing analysis, staff questionnaires ( n = 72), staff interviews ( n = 9), and systematic observation (6 hours). RESULTS: In some patient rooms, access to daylight and/or outdoor views was excellent, while in other rooms such access was hindered by frosted glass or adjacent bushes or buildings. Single-bed rooms gave family members improved privacy and greater ability to stay in the patient room. Some patient room modules provided efficient patient observation and staff collaboration, but more noise and reduced patient privacy. Other modules provided a calm patient room environment, but caused some staff to feel isolated and have difficulty in getting assistance. CONCLUSIONS: The evaluation of the three projects reveals variation in whether design strategies successfully achieve their desired outcomes. Varying designs of the patient room module affect users in unique ways and must balance privacy, visibility, quietness, and staff access to assistance.